Kajian Karakteristik Lanskap Budaya Kampung Adat Ngadu Bolu Di Kabupaten Sumba Tengah - Robert U. Roka Laki Mara; Debora Budiyono; Hendra Kurniawan (Universitas Trisakti, 2024)
Study of the Cultural Landscape Characteristics of the Ngadu Bolu Traditional Village in Central Sumba Regency. Ngadu Bolu Traditional Village, located in Dewa Jara Village, Katikutana District, Central Sumba Regency, is one of the traditional settlements rich in ancestral traditions and culture. The village features distinctive settlement characteristics, with stilt houses and high-pitched roofs, as well as megalithic sites in the form of centuries-old stone graves. The Marapu belief system, which connects humans with their ancestors, also influences the landscape design and architecture of this village. However, modernization has brought significant changes to the physical elements of the village. The traditional thatched roofs have largely been replaced by corrugated iron, the wooden pillars of traditional houses have been replaced by concrete, and some stone graves are now made of cement. These changes threaten the loss of the cultural values inherent in Ngadu Bolu Traditional Village. The cultural landscape, which once reflected local beliefs and traditions, is slowly changing, raising concerns about the erosion of cultural identity. This study aims to examine these changes and formulate conservation strategies to preserve the cultural landscape of Ngadu Bolu Traditional Village. The research results show that the architectural elements and spatial arrangement of the village still strongly reflect the community's beliefs and traditional values, with a unique landscape zoning division: the core zone, buffer zone, and utilization zone. Conservation efforts are urgently needed to ensure the sustainability of the culture while raising public awareness of the importance of preserving ancestral heritage.